Synthesis of zirconium carbide nanoparticles by polymerised complex route. (2nd January 2016) - Liu, R.; Yan, C.; Zhang, C.; Cao, Y.; Long, X.
Abstract : A polymerised complex route, based on polyesterification between tartaric acid–zirconium complex and ethylene glycol (EG), has been demonstrated to synthesise ZrC powders at a relatively low temperature (1300°C). The Fourier transform infrared results confirmed the coordination of tartaric acid to the zirconium ion. Furthermore, this complex reacted with EG through polyesterification to immobilise the metal ion in the rigid polymer. The intimate mixing of the reaction components has thus been achieved in ZrO2 /carbon 'coke" due to the suppression of segregation of the reaction components during pyrolysis. Finally, well crystallised ZrC nanoparticles (50–150 nm) were obtained through the carbothermal reduction of ZrO2 /carbon 'coke', concerning the formation of the intermediate oxycarbide phase.